Spontaneous rupture of leiomyosarcoma - Soe, Ni Ni; Boricha, Yash B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine sarcomas are rare, accounting for approximately 3-7% of uterine malignancies. Leiomyosarcoma (LMS), a particularly aggressive subtype, often presents diagnostic challenges due to overlapping features with benign fibroids. Spontaneous rupture of LMS is exceptionally rare and may lead to life-threatening complications. A 42-year-old woman presented with severe lower abdominal pain, distension, dyspnea, and hemodynamic instability. Imaging revealed a ruptured uterine mass with hemoperitoneum, bilateral pulmonary embolism (PE), and suspected metastatic disease. Initial stabilization required ICU support and multidisciplinary input. Uterine artery embolization was performed to control haemorrhage. The patient developed subsequent infections but stabilized and was repatriated to her home country, where she received six cycles of chemotherapy. Surgery is planned following completion of chemotherapy. This case underscores the diagnostic difficulty in differentiating LMS from benign fibroids, especially in the presence of large, rapidly growing uterine masses. Delayed diagnosis can result in catastrophic events such as spontaneous rupture. Imaging and histology remain essential, but molecular profiling is increasingly valuable for therapeutic planning. Spontaneous rupture of LMS, though rare, should be considered in patients with large symptomatic uterine masses. Early recognition, multidisciplinary management, and genetic profiling are vital for optimizing outcomes. Proactive surgical management of large tumours may help prevent such complications, even in presumed benign cases.